Occurrence and Quantification of Antimicrobial Resistance Genes in the Gastrointestinal Microbiome of Two Wild Seabird Species With Contrasting Behaviors - Ewbank, Ana Carolina; Esperón, Fernando; Sacristán, Carlos; Sacristán, Irene; Neves, Elena; Costa-Silva, Samira; Antonelli, Marzia; Rocha Lorenço, Janaina; Kolesnikovas, Cristiane K. M.; Catão-Dias, José Luiz (Frontiers in Veterinary Science, 2021)
Antimicrobial resistance genes (ARGs) are environmental pollutants and anthropization indicators. We evaluated human interference in the marine ecosystem through the ocurrence and quantification (real-time PCRs) of 21 plasmid-mediated ARGs in enema samples of 25 wild seabirds, upon admission into rehabilitation: kelp gull (Larus dominicanus, n = 14) and Magellanic penguin (Spheniscus magellanicus, n = 11). Overall, higher resistance values were observed in kelp gulls (nonmigratory coastal synanthropic) in comparison with Magellanic penguins (migratory pelagic non-synanthropic). There were significant differences between species (respectively, kelp gull and Magellanic penguin): ARGs occurrence (blaTEM [p = .032]; tetM [p = .015]; tetA [p = .003]; and sulII [p = .007]), mean number of ARGs per sample (p = .031), ARGs mean load percentage (aadA [p = .045], tetA [p = .031], tetM [p = .016], blaTEM [p = .032], sulII [p = .008]), percentage of genes conferring resistance to an antimicrobial class (betalactams [p = .036] and sulfonamides [p = .033]), mean number of genes conferring resistance to one or more antimicrobial classes (p = .024]), percentage of multiresistant microbiomes (p = .032), and clustering (p = .006). These differences are likely due to these species’ contrasting biology and ecology - key factors in the epidemiology of ARGs in seabirds. Additionally, this is the first report of mecA in seabirds in the Americas. Further studies are necessary to clarify the occurrence and diversity of ARGs in seabirds, and their role as potential sources of infection and dispersal within the One Health chain of ARGs.